Self-assembly system based on water-soluble perylene diimide for sensitive detection and discrimination of tea polyphenols. (February 2021) - Yan, Mi; Shen, Xue; Zhong, Shuning; Diao, Mengxue; Zhao, Changhui; Xu, Yanyang; Zhang, Tiehua
Abstract: Tea polyphenols have become one of the promising healthcare molecules due to their anti-cancer, anti-oxidant, and anti-obesity capacities, making tea among the most popular and functional beverages worldwide. However, the sensitive and simple detection and discrimination of tea polyphenols is difficult to achieve since the analogues usually have similar chemical structures with polyhydroxy. Herein, a self-assembly system based on a cationic perylene diimide molecule tagging with phenylboric acid group (PDI-PBA) was constructed for detection and discrimination of catechin molecules (Epicatechin, Epicatechin gallate, Epigallocatechin, Epigallocatechin gallate), a subgroup of tea polyphenols. PDI-PBA could recognize tea polyphenols by dynamic borate ester bonds between PBA groups on PDI-PBA and cis -diols on tea polyphenols. Moreover, the fluorescence quench ratios of PDI-PBA were determined by the different aggregation degrees induced by every tea polyphenol with the unique chemical structure, especially cis -diol numbers. Thus, the selective discrimination could be easily realized by linear discriminant analysis (LDA). The developed system relies mainly on dynamic borate ester bonds between the probe and substrates, the self-assembly of PDI-PBA, and polyhydroxy characteristic of tea polyphenols. This work provides a new strategy for sensitive detection and discrimination of tea polyphenols. Graphical abstract: Image 1 Highlights: A PDI-PBA based self-assembly systems was constructed for sensitive detection and discrimination of tea polyphenols. The fluorescence responses of PDI-PBA were determined by its aggregation degrees induced by tea polyphenols. The system relies on dynamic borate ester bonds, self-assembly of PDI-PBA, and polyhydroxy of tea polyphenols.